Why Was It So Easy? The Strong and Weak Points of Revising the Interpretation of the Dictatorship of the Communist Party of Czechoslovakia and Its Accession to Power in February 1948 - Sedlák , Petr (Dějiny – teorie – kritika, 2023)
The main aim of this study is to provide an overview of historiographic treatment of the dictatorship of the Communist Party of Czechoslovakia by several contemporary historians. They criticise the current ‘totalitarian-historical’ interpretation and claim it is inaccurate and misleading because in order to provide a political legitimisation and social exculpation, it exaggerates the role and the extent of repression in this dictatorship. This critical tendency in current historiography can be seen as revisionist. The article evaluates the strong and the weak points of revision using the example of the immediate aftermath of the WWII, when the Communist dictatorship was beginning to take hold. The author addresses the question ‘why was it so easy?’, that is, why such a large part of the Czech society supported the dictatorship or stood by and did not protest against its establishment in February 1948. In particular, the study searches for historiographic options and dangers in the work of select revisionist historians on the level of theoretical questions and consequent methodological applications.